Correlation of serotype-specific dengue virus infection with clinical manifestations. - Eric S Halsey; Morgan A Marks; Eduardo Gotuzzo; Victor Fiestas; Luis Suarez; Jorge Vargas; Nicolas Aguayo; Cesar Madrid; Carlos Vimos; Tadeusz J Kochel; V Alberto Laguna-Torres (Public Library of Science (PLoS), 2012)
Disease caused by the dengue virus (DENV) is a significant cause of morbidity throughout the world. Although prior research has focused on the association of specific DENV serotypes (DENV-1, DENV-2, DENV-3, and DENV-4) with the development of severe outcomes such as dengue hemorrhagic fever and dengue shock syndrome, relatively little work has correlated other clinical manifestations with a particular DENV serotype. The goal of this study was to estimate and compare the prevalence of non-hemorrhagic clinical manifestations of DENV infection by serotype.Between the years 2005-2010, individuals with febrile disease from Peru, Bolivia, Ecuador, and Paraguay were enrolled in an outpatient passive surveillance study. Detailed information regarding clinical signs and symptoms, as well as demographic information, was collected. DENV infection was confirmed in patient sera with polyclonal antibodies in a culture-based immunofluorescence assay, and the infecting serotype was determined by serotype-specific monoclonal antibodies. Differences in the prevalence of individual and organ-system manifestations were compared across DENV serotypes. One thousand seven hundred and sixteen individuals were identified as being infected with DENV-1 (39.8%), DENV-2 (4.3%), DENV-3 (41.5%), or DENV-4 (14.4%). When all four DENV serotypes were compared with each other, individuals infected with DENV-3 had a higher prevalence of musculoskeletal and gastrointestinal manifestations, and individuals infected with DENV-4 had a higher prevalence of respiratory and cutaneous manifestations.Specific clinical manifestations, as well as groups of clinical manifestations, are often overrepresented by an individual DENV serotype.